2009
DOI: 10.1021/ef900619y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Synthesis of Sodium Borohydride by Recycling Sodium Metaborate

Abstract: Hydrogen can be easily produced from the catalytic hydrolysis of sodium borohydride (NaBH 4 ), with sodium metaborate (NaBO 2 ) being the co-product. If NaBO 2 can be economically recycled in the process, NaBH 4 could be considered as a promising hydrogen carrier in fuel cells because of its high hydrogen content. In this paper, we report our investigation into the synthesis of NaBH 4 from NaBO 2 via ball milling. The starting materials for the synthesis were NaBO 2 and magnesium hydride (MgH 2 ). After ball m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 17 publications
(31 reference statements)
0
37
0
Order By: Relevance
“…NaBH 4 Regeneration via the Reaction between Mg 2 Si and NaBO 2 ·2H 2 O Via ball milling hydrated NaBO 2 and Mg, NaBH 4 was regenerated and the energy efficiency was further increased. However, the highest NaBH 4 yield by this method was 68.55%, which did not reach the general yield of regenerated NaBH 4 (~76%) [67,68]. According to Kojima et al [66], with Si added, the NaBH 4 yield was increased in the reaction between NaBO 2 and Mg under a hydrogen atmosphere.…”
Section: Nabh 4 Regeneration Via the Reaction Between Mg And Nabo 2 ·mentioning
confidence: 77%
See 1 more Smart Citation
“…NaBH 4 Regeneration via the Reaction between Mg 2 Si and NaBO 2 ·2H 2 O Via ball milling hydrated NaBO 2 and Mg, NaBH 4 was regenerated and the energy efficiency was further increased. However, the highest NaBH 4 yield by this method was 68.55%, which did not reach the general yield of regenerated NaBH 4 (~76%) [67,68]. According to Kojima et al [66], with Si added, the NaBH 4 yield was increased in the reaction between NaBO 2 and Mg under a hydrogen atmosphere.…”
Section: Nabh 4 Regeneration Via the Reaction Between Mg And Nabo 2 ·mentioning
confidence: 77%
“…Therefore, the thermochemistry method was substituted by room temperature ball milling in this reaction. Hsueh et al [67], Kong et al [68] and Çakanyildirim et al [69] used MgH2 to react with NaBO2 by ball milling under argon. All of their NaBH4 yields were over 70%, which strongly indicated that ball milling is suitable for the reaction between MgH2 and NaBO2.…”
Section: Nabh4 Regeneration Via the Reaction Between Metal Or Other Hmentioning
confidence: 99%
“…Moreover, the multiphysical fields can be studied by the coupled method for designing and optimizing the magnesium electrolysis cell. (2) According to the temperature distribution of the magnesium electrolysis cell, the highest temperature appeared in the electrolyte domain. A huge amount of heat was lost from anodes because the average temperature of the anode surfaces exposed to air is 251°C, which is much higher than other surfaces of the cell.…”
Section: Resultsmentioning
confidence: 99%
“…Use of this type of mill for MgH 2 reduction of NaBO 2 to form NaBH 4 has been described in the literature. [46,47] The planetary mill jar serves as the reaction vessel ( Figure 3.4.1b and c). During operation, the jar or "planet" spins in a horizontal plane while orbiting the "sun" on a rotating disc in the opposite direction in the ratio 1:-2 (disc revolutions: jar revolutions).…”
Section: Planetary Ball Millmentioning
confidence: 99%